The Impact of Morale and Work Experience on Hotel Employee Performance - Faozen, Faozen (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2023)
Human resources are an important aspect of the industry to achieve industrial goals, where industrial goals are carried out if in the industry there are potential and professional human resources, it can provide quality improvement and industrial quality. The objectives of this study include determining the relationship between morale and employee performance, to find out the experience of work on employee performance. This research method uses a total sample of 82 respondents with a saturated sampling method. The results of this research prove that variable morale has a positive and significant impact on employee performance where if morale increases, employee performance will also increase, activity experience affects positively and is important to employee abilities whereas if work experience increases employee performance will also increase. Assessing that morale and good work experience will improve employee performance in hotels. Keywords: Morale; Work Experience; Performance; Employees; Hotels